코로나19발생에 의한 어촌관광 변화추이 빅데이터 분석연구 - 최규철(Choi, Kyu Chul); 이서구(Lee, Seo Gu); 강동선(Kang, Dong Seon) (한국디자인리서치, 2021)
코로나19로 인하여 전 산업분야가 타격을 받고 있으며, 더욱이 비대면 방식의 ‘언택트(Untact)’ 문화로 여가생활의 많은 변화가 생겨나고 있다. 이는 우리의 어촌체험휴양마을에도 부정적인 영향을 주고 있을 가능성이 제기된다. 대표적인 경험재로서의 문화소비인 체험관광, 그 중에서도 우리의 어촌에서 즐기는 것이 어업인에게 어업외 소득까지 연결되니 사회적으로 가치있는 관광소비의 형태임을 인지한다면 어촌관광의 쇠락이 우리사회에 미치는 영향이 상당하다 할 수 있다. 어촌관광의 새로운 도약를 위해 빅데이터의 고도화된 분석과 대안제시는 중요하며, 코로나19로 인해 타격을 받은 어촌관광산업의 활성화를 위해서 본 연구가 시작되었다. 기존 설문조사 등의 소비자 니즈분석을 빅데이터(모바일 통신데이터와 카드매출데이터)기반의 소비자 분석으로 코로나19로 인한 방문객 수, 매출액의 변화추이를 확인하였다. 당초 연구는 코로나19로 인해서 거제시 다대어촌체험휴양마을의 방문객 및 매출액이 현저히 감소했을 것이라는 가설을 가지고 연구가 진행되었지만 감소인자(코로나19)에 대한 증감인자(아웃바운드 관광수요 및 지속적인 코로나19로 인한 피로감 등)로 상쇄되어 2년의 조사기간 동안(2018.9월~2020.9월)방문객 수, 매출액이 코로나19 전후로 유의미한 변화는 없는 것으로 나타났다. 또한, 분석결과에 대한 각 주체별로 활용할 수 있도록 시사점을 도출하였다. 해양관광 관련 정책개발 담당자, 어촌체험휴양마을 관리운영자에 대한 유의미한 데이터 제공 및 분석근거를 보여주고자 하였다. 특히, 현재 여러가지 기술적 한계점에 대해서는 향후 제도적 보완을 통해 보다 쉽게 빅데이터를 제공받고 활용할 수 있다면 마케팅, 관광산업 뿐만 아니라 전산업에 걸쳐 패러다임의 변화를 줄 계기가 될 수 있다고 생각된다. Corona 19 is hurting the entire industry, and moreover, many changes in leisure life are being made due to the non-face-to-face "untact" culture. This raises the possibility that it is negatively affecting our fishing village recreation village. Considering that what we enjoy in our fishing villages is a form of socially valuable tourism consumption, the decline of fishing village tourism can have a significant impact on our society. Advanced analysis of big data and proposal of alternatives are important for a new leap forward in fishing village tourism. Changes in the number of visitors and sales due to COVID-19 were confirmed by analyzing consumer needs, such as existing surveys, based on big data (mobile communication data and card sales data). Initially, the study was conducted with the hypothesis that the number of visitors and sales of the Dadae Fishing Village Experience Recreation Village in Geoje would have significantly decreased due to Corona 19. Fatigue, etc.), there was no significant change in the number of visitors and sales during the two-year survey period (September 2018 to September 2020) before and after Corona 19. In addition, implications were drawn so that the analysis results could be utilized for each subject. The purpose of this study was to provide meaningful data and to show the basis of analysis for marine tourism related policy development managers and fishing village experience resort village managers. In particular, for various technical limitations, if big data can be more easily provided and utilized through institutional supplementation in the future, it can be an opportunity to change the paradigm not only in the marketing and tourism industries but also across all industries. KCI Citation Count: 0